Latin-American Undergraduate Nurse Network: description and analysis - Muñoz, Mónica; Cabieses, Báltica; Calderón, Jennie; Torres, Marisieska (Investigación y Educación en Enfermería, 2008)
The Latin-American Undergraduate Nurse Network is an international association that works for improving health development in Latin America. It works as an independent and collaborative network, and through time it has developed several goals for nurses around the world. Nowadays they get more strengths and weaknesses as well as environmental opportunities and threatenes determine its surviellence and growing. The objectives of this article are: to describe The Latin-American Undergraduate Nurse Network through its 4 years of network and to develop an analysis of its strengths, weaknesses, opportunities and threatens, in order to establish several recommendations for this network improvement and strengthen. Key words: network, nursing undergraduates, FODA analysis.